Analysis of it sector development in Ukraine - Sheiko, I. А.; Storozhenko, O. V. (ХНУРЕ, 2021)
The Ukrainian IT sphere is called the most promising sector for the development of the domestic economy. According to the Cabinet of Ministers, in 2019, information technologies accounted for 3.9% of GDP - UAH 138 billion
Keywords: domestic economy; бізнес-освіта; стратегії економічного розвитку